Benefit of Nigella sativa for Chronic Obstructive Pulmonary Disease Patients: A Narrative Review - Sandy Laveda; Wayan Wahyu Semara Putra; Tungki Pratama Umar (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory disease that has a significant global impact. Unfortunately, current treatments and prevention remain insufficient. Nigella sativa (NS) has been traditionally used as an anti-inflammatory, antioxidant, and immunomodulatory agent, which can be helpful in the treatment of COPD, through its essential component thymoquinone. This review examined the potential benefits of NS for COPD patients as a possible treatment option. Methods: The literature investigation was conducted by searching relevant articles on Google Scholar and NCBI using the keywords